Karaite Judeo-Arabic Translations of Mishnah Rosh ha-Shanah: On the Meaning of Ba'alil - Tirosh-Beker, Ofrah (The Jewish quarterly review, 2005)
Karaite scholars of the tenth and the eleventh centuries were well acquainted with rabbinic literature. This is evident from their writings in which they cite excerpts from the Mishnah and other rabbinic sources. These citations were occasionally accompanied by Karaite Judeo-Arabic translations, which are of special interest as medieval rabbinic Judeo-Arabic translations of the Mishnah are not common. In this paper we present Judeo-Arabic translations of Mishnah Rosh ha-Shanah 1.5 written by the five renowned Karaite scholars Yusuf al-Basir, Ya'qub al-Qirqisani, Yeshu'ah ben Yehudah, Levi ben Yefet and David ben Avraham al-Fasi, all from the tenth and the eleventh centuries. The word ba'alil, whose Karaite translations are discussed here in details, appears three times in this mishnah, which relates to the sanctification of the new lunar month. This word is a hapax legomenon in the Bible (Ps 12.7) and its occurrences in rabbinic literature are few. This study shows that the Karaite Judeo-Arabic translations of ba'alil reflect two main interpretations, both pertaining to first visibility. One explains ba'alil as reflecting attributes of the new moon, while the other views this word as indicating the relative position of the new moon in the sky. From this discussion we also learn of the Karaite attitude towards the rabbinic text. Not only did these Karaites cite from the Mishnah they also translated passages from it and discussed the exact meaning of key terms that appear in these texts.